2013
DOI: 10.1136/bmjopen-2013-003370
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic portosystemic shunt for the prevention of variceal rebleeding in cirrhotic patients with portal vein thrombosis: study protocol for a randomised controlled trial

Abstract: IntroductionPortal vein thrombosis (PVT) increases the risk of variceal rebleeding in liver cirrhosis. However, the strategy for preventing variceal rebleeding in cirrhotic patients with PVT has not been explored. This study aims to evaluate whether the transjugular intrahepatic portosystemic shunt (TIPS) or conventional therapy is preferable for the prevention of variceal rebleeding in liver cirrhosis patients with PVT.Methods and analysisThis is a randomised controlled trial comparing the safety and efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…No control group was established in this study. However, a randomized controlled trial, which compares the outcome of TIPS with that of pharmacological/endoscopic therapy in combination with anticoagulation for the secondary prophylaxis of variceal bleeding in cirrhotic patients with PVT, is being conducted at our centre . All patients have been successfully enrolled till January 2014, and they are being followed.…”
Section: Discussionmentioning
confidence: 99%
“…No control group was established in this study. However, a randomized controlled trial, which compares the outcome of TIPS with that of pharmacological/endoscopic therapy in combination with anticoagulation for the secondary prophylaxis of variceal bleeding in cirrhotic patients with PVT, is being conducted at our centre . All patients have been successfully enrolled till January 2014, and they are being followed.…”
Section: Discussionmentioning
confidence: 99%
“…Its advantages are that the occluded vessels can be easily recanalized by endovascular techniques, and the patency of vessels can be effectively maintained by an accelerated blood flow through the main portal vein and shunt. However, its primary treatment goal remains to resolve the portal hypertension-related complications [ 39 ] because no controlled trials are available to confirm the benefits of TIPS versus anticoagulation for recanalizing the thrombosed portal vein [ 40 ]. Despite that, our systematic review showed that the survival of cirrhotic patients who were treated with TIPS or surgical shunts was not influenced by the presence of a preexistent PVT.…”
Section: Discussionmentioning
confidence: 99%
“…Poor hepatic function (MELD >18) and presence of encephalopathy limit use in all patients. We await the results from a prospective randomized control trial conducted in China with great anticipation [69].…”
Section: Mechanical Therapymentioning
confidence: 99%